P-103 A community of practice: building capability to provide high quality dementia care. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Cooper, Marie; Dening, Karen Harrison
Abstract : In recent years there has been a significant increase in policy and guidance, across many countries, to promote palliative and end-of-life care for non-malignant life-limiting conditions. Most notably for people with dementia (PWD) at the end-of-life and facilitate better access to palliative care. PWD, particularly those in the advanced stages, may experience poor end-of-life care because they may not be perceived to have a terminal illness. There is concern in some settings and services that staff are ill – equipped to care for PWD, in respect of knowledge and skills. Both Hospice UK and Dementia UK thus launched the 'Dementia in palliative and end-of-life care Community of Practice' to bring together practitioners keen, in the spirit of mutual learning, to share knowledge and practice and provide high quality palliative and end-of-life care for families affected by dementia. At the inaugural meeting a nominal group technique was used to identify learning needs across both groups of clinicians. Thirteen learning needs were identified, of which five were ranked as priorities to be met during future meetings. Shared learning through a community of practice is a way of harnessing the expertise across the two care domains, with the common objective of improving the lives, and deaths of PWD and in better support of their families. We hold two community meetings a year and due to increase in engagement will be hosting a conference in 2017. Events are well evaluated and membership is growing.